Comparative real-world effectiveness of ustekinumab versus anti-TNF in Crohn’s disease: 12-month maintenance phase results from the prospective, observational RUN-CD study using propensity score adjustment - Bokemeyer, Bernd; Plachta-Danielzik, Sandra; Gilman, Elena; di Giuseppe, Romina; Deppe, Herbert; Mohl, Wolfgang; Teich, Niels; Hoffstadt, Martin; Schweitzer, Axel; von der Ohe, Manfred; Gauss, Annika; Atreya, Raja; et al. (Journal of Crohn's and Colitis, 2025)
The prospective RUN-CD registry investigates the effectiveness of ustekinumab (UST) and other biologics in Crohn’s disease (CD) across Germany. Based on data from the registry, this study presents the maintenance phase results of a 12-month real-world-evidence (RWE) comparison of CD patients initiating new biologic therapies with UST or anti-TNF.After excluding patients using biologics other than UST and anti-TNF and those with missing outcomes, the final sample consisted of 618 CD patients. Clinical remission (CR), defined as a Harvey-Bradshaw Index (HBI) ≤4, was the prespecified endpoint at 12 months. Switching to another biologic therapy was considered an outcome failure. Propensity score adjustment was used to reduce the effect of confounders.The study included 343 CD patients treated with UST and 264 treated with anti-TNF. Over 12 months, the frequency of therapy switches was significantly higher for infliximab (28%) compared with UST (17%) and adalimumab (17%) (P =.045). There was no significant difference in CR rates at 12 months between the UST and anti-TNF groups (65.8% vs 60.0%, P =.262). However, in week-16 responders, CR rates at 12 months were significantly higher with UST (77.6%) versus anti-TNF (65.4%) (P =.041). The change in EQ-VAS (QoL) scores between UST and anti-TNF showed a 5.1-point difference favoring UST (P =.002).In this 12-month RWE comparison, overall CR rates were similar between UST and anti-TNF. However, among week-16 responders, CR rates were significantly higher with UST. Additionally, UST was associated with a significantly greater improvement in QoL compared with anti-TNF.